THE MOTION OF DUST PARTICLES ORBITING СYLINDRICAL PROBE IN GLOW DISCHARGE PLASMA - Kodanova, S.K. (Recent Contributions to Physics, 2008)
In the present work the behavior of dust particles near Langmuir cylindrical probe in glow discharge plasma was numerically investigated. The potential distribution near probe was founded, the dependences of dusty particle’s charge from some distance to probe were determined. Trajectories of dust particles for different initial kinetic energies and impact parameters were calculated. It was impossible the discharge for particles with great energy at some values of distance to probe.